2013
DOI: 10.7314/apjcp.2013.14.11.6257
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Chemical Composition of Gallbladder Stones and their Association with Induction of Cholangiocarcinoma

Abstract: Gallstone disease is a major surgical problem in many populations; it is probably related to diet, especially excessive consumption of meat. The objective of this study was to determine the chemical composition of gallstones and their association with neoplastic changes including cholangiocarcinomas in cholecystectomised patients. The chemical composition of gallstones from 40 patients (8 males and 32 females) was analyzed. This is a prospective study performed in Baquba teaching hospital in the period from 1/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…According to the data available (Poloni and Ward 2014 ), the unwanted depositions could consist of many substances and all of them always lead to various diseases. Regarding the unwanted depositions of CaPO 4 , they are found in soft tissue calcification (in damaged joints, blood vessels, dysfunctional areas in the brain, diseased organs, scleroderma, prostate stones) (Reid and Andersen 1993 ; Scotchford and Ali 1995 ; P’ng et al 2008 ; Brancaccio and Cozzolino 2005 ; Goff and Reichard 2006 ; Bittmann et al 2003 ; Molloy and McCarthy 2006 ; Giachelli 2004 ; Kazama et al 2007 ), kidney (Giannossi and Summa 2012 ; Mukherjee 2014 ) and urinary (Zhu et al 2014 ; Huo et al 2015 ; Selvaraju et al 2015 ) stones, dental pulp stones and dental calculus (Kakei et al 2009 ; Kodaka et al 1988 , 1998 ; Çiftçioglu et al 1998 ; Hayashizaki et al 2008 ), salivary stones (Zelentsov et al 2001 ; Luers et al 2014 ), gall stones (Qiao et al 2013 ; Hussain and Al-Jashamy 2013 ), pineal gland calcifications (Güney et al 2013 ), atherosclerotic arteries and veins (Ortlepp et al 2004 ; Tomazic 2001 ; Marra et al 2006 ; Kurabayashi 2013 ), coronary calcification (Fitzpatrick et al 2003 ; Matsui et al 2015 ), damaged cardiac valves (Suvorova and Buffat 2005 ), calcification on artificial heart valves (Giachelli 2001 ; Pettenazzo et al 2001 ; Schoen and Levy 2005 ; Delogne et al 2007 ), carpal tunnel (Sensui et al 2003 ; Namba et al 2008 ) and tumoral (Namba et al 2008 ; Carlson et al 2007 ; Sprecher 2010 ; Slavin et al 2012 ; Kim et al 2013 ; Burns et al 2013 ) calcifications, cataracts (Kim and Choi 2007 ; Koinzer et al 2009 ), malacoplakia (Ho 1989 ), calcified menisci (Katsamenis et al 2...…”
Section: Pathological Calcification Of Capomentioning
confidence: 99%
“…According to the data available (Poloni and Ward 2014 ), the unwanted depositions could consist of many substances and all of them always lead to various diseases. Regarding the unwanted depositions of CaPO 4 , they are found in soft tissue calcification (in damaged joints, blood vessels, dysfunctional areas in the brain, diseased organs, scleroderma, prostate stones) (Reid and Andersen 1993 ; Scotchford and Ali 1995 ; P’ng et al 2008 ; Brancaccio and Cozzolino 2005 ; Goff and Reichard 2006 ; Bittmann et al 2003 ; Molloy and McCarthy 2006 ; Giachelli 2004 ; Kazama et al 2007 ), kidney (Giannossi and Summa 2012 ; Mukherjee 2014 ) and urinary (Zhu et al 2014 ; Huo et al 2015 ; Selvaraju et al 2015 ) stones, dental pulp stones and dental calculus (Kakei et al 2009 ; Kodaka et al 1988 , 1998 ; Çiftçioglu et al 1998 ; Hayashizaki et al 2008 ), salivary stones (Zelentsov et al 2001 ; Luers et al 2014 ), gall stones (Qiao et al 2013 ; Hussain and Al-Jashamy 2013 ), pineal gland calcifications (Güney et al 2013 ), atherosclerotic arteries and veins (Ortlepp et al 2004 ; Tomazic 2001 ; Marra et al 2006 ; Kurabayashi 2013 ), coronary calcification (Fitzpatrick et al 2003 ; Matsui et al 2015 ), damaged cardiac valves (Suvorova and Buffat 2005 ), calcification on artificial heart valves (Giachelli 2001 ; Pettenazzo et al 2001 ; Schoen and Levy 2005 ; Delogne et al 2007 ), carpal tunnel (Sensui et al 2003 ; Namba et al 2008 ) and tumoral (Namba et al 2008 ; Carlson et al 2007 ; Sprecher 2010 ; Slavin et al 2012 ; Kim et al 2013 ; Burns et al 2013 ) calcifications, cataracts (Kim and Choi 2007 ; Koinzer et al 2009 ), malacoplakia (Ho 1989 ), calcified menisci (Katsamenis et al 2...…”
Section: Pathological Calcification Of Capomentioning
confidence: 99%
“…Epidemiological studies have found that primary sclerosing cholangitis (PSC), liver flukes infestation and cholecystitis are well-established (Tyson et al, 2011;Songserm et al, 2012;Hussain et al, 2013;Manwong et al, 2013). Also, hepatitis virus infection may also play a role in the development of CC (Srivatanakul et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…PTCD/ PTBS is a method of biliary tree decompression, applied as palliative treatment in patients with inoperable malignant biliary obstruction, which could not only significantly reduce bilirubin level, improve the patients life quality and prolong survival time, but also provide the possibillity for subsequent treatment (Hatzidakis et al, 2001;Iruarrizaga et al, 2011). In clinical, patients with obstructive jaundice caused by hilar cholangiocarcinoma are common, most of them have lost the chance of operation (Butthongkomvong et al, 2013;Chong et al, 2013;Duangsong et al, 2013;Huang et al, 2013;Hussain et al, 2013;Kamsa-ard et al, 2013;Manwong et al, 2013;Prachayakul et al, 2013;Sriraksa et al, 2013;Srikoon et al, 2013;Sriputtha et al, 2013;Subrungruanga et al, 2013;Thunyaharn et al, 2013;Woradet et al, 2013). Obstructive jaundice caused by hilar cholangiocarcinoma not only affects the patient's liver function, but also influence the patient's survival time.…”
Section: Discussionmentioning
confidence: 99%